Management of internet names and addresses : intellectual property issues : final report (WIPO GenevaCH, 1999)
Makes recommendations with regard to - best practices for registration authorities; administrative procedure concerning abusive domain name registrations; exclusions for famous and well-known marks; new generic Top-Level Domains; and, the first steps and outstanding issues.
Keywords: INTERNET